Pengaruh Putaran Mesin Terhadap Produksi Bio-Oil Bungkil Kemiri Sunan Menggunakan Reaktor Rotary Pirolisis - Luhulima, Yosua William; Winaya, I N. Suprapta; Tenaya, I G.N.P. (Teknik Desain Mekanika, 2021)
Abstract As time goes by and as technology advances, the need for energy is increasing out of control, as a result reserves of fossil fuels in the bowels of the earth are running low. Therefore, the government has begun to develop kemiri sunan biodiesel so that it can meet human needs for energy. However, processing kemiri sunan biodiesel by pressing produces waste in form of kemiri sunan cake, which still contains oil that cannot be further removed through the pressing process. One way to get this oil out is through the pyrolysis process. This study aims to determine the effect of rotation on the mass of bio-oil (condensate) through rotary pyrolysis using iron sand. Through this rotation variation it is expected that the resulting condensate mass will increase along with increase in rotation given and it is hoped that mixing the fuel with the bed material will produce a more even heating so that it produces more condensate. The variation used is rotation variation. At rotation variation, the reactor operation is carried out, namely at 1600rpm, 1800rpm, 2000rpm and 2400rpm. The conclusion from the test results data is that the pyrolysis results at 2400 rpm is better and more efficient than at other rotations. This is because a more even heating process can make the gas yield more abundant so that the resulting condensate increases and the charcoal produced is also reduced and the time needed in the process is shorter. Keywords: Rotations, rotary pyrolysis, bio-oil (condensate)